Ultrafiltration of Opuntia ficus-indica mucilage obtained by solvent-free mechanical extraction - Carpintero-Tepole, Violeta; Córdova-Aguilar, María Soledad; Vázquez-León, Lucio Abel; Guzmán-Huerta, Citlali; Blancas-Cabrera, Abel; Ascanio, Gabriel (Journal of Food Processing and Preservation, 2021)
The ultrafiltration (UF) of cactus juices has been carried out for the purpose of clarification from an enzymatically pre-treated fruit. Concentration of mucilage (Opuntia ficus-indica) by cross-flow ultrafiltration, obtained by solvent-free mechanical extraction, using 1, 10, and 30 kDa membranes has been carried out. The ηE was 39.49% and the energy consumption was 247 times less than the evaporation one. The 1 kDa concentrated mucilage had the highest ηUF and total soluble solids although the fastest process was with the 30 kDa membrane which also extends its shelf life up to 60 days at 4°C, preserving its viscous and viscoelastic properties and high contents of galacturonic acid, features desired to be applied as a dispersing agent. Chromatographic analysis shown that the passage of the monosaccharides during the ultrafiltration was in function of their position in the structure of mucilage molecule. Sugars such as galacturonic acid and galactose were conserved after filtration; however, decreased the concentration of sugars that make up the side chains (rhamnose, glucose, arabinose, and xylose) of the mucilage molecule.
Keywords: Ultrafiltración; Jugo de cactus; Mucílago